ANALISIS PENGARUH TINGKAT PERTUMBUHAN EKONOMI TERHADAP PENGANGGURAN DI SUMATERA UTARA - Elsa Mila Switta Sembiring; Rusiade Rusiade; Bachtiar Effendi (Ensiklopedia Education Review, 2021)
Economic growth is a benchmark in knowing how developed and developing a region the level of economic growth is strongly influenced by internal and external factors this study aims to determine the effect of economic growth on the level of unemployment in north Sumatra the data used in study is secondary data obtained from the central bureau of statistics of north Sumatra . the management of this research data uses the SPSS V-19 program. From the results of the analysis carried out, it can be concluded that the partial test(t test) is know that economic growth has a negative effect on the number of unemployed in north sumatra Keywords: Economic Growth, Unemployment.